Clarifying realist analytic and interdisciplinary consensus processes in a complex health intervention: A worked example of Judgemental Rationality in action. (October 2021) - Rybczynska-Bunt, Sarah; Weston, Lauren; Byng, Richard; Stirzaker, Alex; Lennox, Charlotte; Pearson, Mark; Brand, Sarah; Maguire, Mike; Durcan, Graham; Graham, Jonathan; Leonard, Sarah; Shaw, Jenny; et al.
Judgemental rationality is infrequently referenced within discussions of Realist Evaluations. Judgemental rationality refers to researchers' capacity to assess which, potential, meanings provide the most credible explanations. In evaluation work, rationale for analysis is provided, though rarely do we see how an evaluator made judgements between competing theories, and which theories were discarded and why. We provide a worked example of the application of judgemental rationality. The Engager intervention offered support to prison leavers with common mental health problems. The data for 24, purposively sampled, participants from the intervention arm of the trial were integrated. Bhaskar's DREIC, a five-step analytical procedure, was used to transfactually theorise and interrogate the inferences made within, and across, cases. The findings demonstrated that the intervention was more effective when practitioners developed an in-depth understanding of the participant. We recommend that intervention developers look for ways to enhance therapeutic competencies and judgemental rationality in practitioner teams.